The imagination of urban chaos : representations of terrorism in late Victorian and modernist literature - Ó Donghaile, Deaglán (Trinity College (Dublin, Ireland). School of English, 2005)
Modern terrorism emerged in the 1880s and 1890s, when outbreaks of apparently sporadic violence by nihilists, Irish republicans and anarchists changed the way in which the public viewed the issue of political subversion. Russian nihilists opened the age of terrorism with the assassination of Tsar Alexander II, who was killed by a bomb in St Petersburg in 1881, and shortly afterward Britain was terrorized by Irish republican terrorism when, from 1883-1885, Clan na Gael launched its brief but spectacular dynamite campaign by setting off a series of explosions in several cities. This outbreak was soon followed by the political violence and revolutionary rhetoric of the anarchists, whose “propaganda-by-deed” continued up until the end of the 1890s. The political atmosphere of this period was also expressed in literature - in popular novels, in the anarchists’ own journalism and, finally, in the pages of the modernist journal, BLAST. This thesis examines the literature, published during the late Victorian and early Modernist periods, that explored the issue of political violence: its presence was felt in popular novels, journalism and literary modernism, introducing to literature the character of the modern terrorist, who became an emblematic figure of fin de siecle.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin